SIMULASI KOORDINASI PROTEKSI SISTEM TENAGA LISTRIK MENGGUNAKAN ETAP - Pertiwi Nurul Utami; Yonki Alexander Volta; Muhammad Hanif Fatin (LPPM POLBITRADA, 2024)
The electric power system must be very reliable, both in the aspects of generation, transmission and distribution. In this way, continuity of the electrical power supply to consumers can be guaranteed. One way that can be taken is to pay attention to the protection of the electric power system itself. This research aims to determine whether the coordination of electrical power system protection equipment is optimal or not. In this research, the method applied is simulation using the ETAP (Electric Transient Analysis Program) application. The process includes creating a power system circuit then applying several disturbances to the power system, then observing the existing protection equipment and analyzing system power data, disturbances, and electrical power protection equipment. This analysis is carried out by paying attention to the working order of the protective equipment during several disturbances and also the working time of the protective equipment. Coordination of power system protection equipment works well. In the simulation system according to the order of work, namely fuse, recloser and circuit breaker (CB). The last sequence of protective equipment that works is CB which has been set at 0.2 seconds. In each fault simulation, the first protection device to work is the fuse at 10 ms. If there is a security failure by the fuse, the recloser will work in 110ms seconds